BSA-templated MnO2 nanoparticles as both peroxidase and oxidase mimics - Liu, Xing; Wang, Qi; Zhao, Huihui; Zhang, Lichun; Su, Yingying; Lv, Yi (Analyst (London), 2012)
Inorganic nanomaterials that mimic enzymes are fascinating as they potentially have improved properties relative to native enzymes, such as greater resistance to extremes of pH and temperature and lower sensitivity to proteases. Although many artificial enzymes have been investigated, searching for highly-efficient and stable catalysts is still of great interest. In this paper, we first demonstrated that bovine serum albumin (BSA)-stabilized MnO(2) nanoparticles (NPs) exhibited highly peroxidase-, oxidase-, and catalase-like activities. The activities of the BSA-MnO(2) NPs were evaluated using the typical horseradish peroxidase (HRP) substrates o-phenylenediamine (OPD) and 3,3',5,5'-tetramethylbenzidine (TMB) in the presence of either hydrogen peroxide or dissolved oxygen. These small-sized BSA-MnO(2) NPs with good dispersion, solubility and biocompatibility exhibited typical Michaelis-Menten kinetics and high affinity for H(2)O(2), OPD and TMB, indicating that BSA-MnO(2) NPs can be used as satisfactory enzyme mimics. Based on these findings, BSA-MnO(2) NPs were used as colorimetric immunoassay tags for the detection of goat anti-human IgG in place of HRP. The colorimetric immunoassay using BSA-MnO(2) NPs has the advantages of being fast, robust, inexpensive, easily prepared and with no HRP and H(2)O(2) being needed. These water-soluble BSA-MnO(2) NPs may have promising potential applications in biotechnology, bioassays, and biomedicine.